MODERN DIAGNOSTICS METHODS OF NON-SPECIFIC PROTECTION OF PERIODONTAL TISSUES IN RESIDENTS OF THE INDUSTRIAL REGION - A.V. Samoilenko; S.V. Pavlov; I.V. Vozna (Український стоматологічний альманах)
The aim of the article is to study the peculiarities of antimicrobial immunity of the oral cavity of the industrial region’s inhabitants in order to optimize special preventive programs of major dental diseases.